2011
DOI: 10.2174/187231211796904982
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Renal Alkaline Phosphatase by Cimetidine

Abstract: Alkaline phosphatase (ALP) belongs to hydrolase group of enzymes. It is responsible for removing phosphate groups from many types of molecules, including nucleotides and proteins. Cimetidine (trade name Tagamet) is an antagonist of histamine H2-receptor that inhibits the production of gastric acid. Cimetidine is used for the treatment of gastrointestinal diseases. In this study the inhibitory effect of cimetidine on mouse renal ALP activity was investigated. Our results showed that cimetidine can inhibit ALP b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Oral gavage, 20 mg/kg/day dissolved in 2 ml saline (Sahin et al, 2019); Orally via catheter, 20 mg/kg (Tok et al, 2012) Ameliorated glomerular and tubular histology, decreased kidney expression of caspase-1 and fraction of TUNEL-positive cells (apoptosis) and kidney expression of NLRP3 and IL-1β (inflammation) in a rat model of diabetes (Sahin et al, 2019); reduced levels of lipid peroxidation and oxidative injury products in renal tissue, improved histological appearance in a rat I/R model (Tok et al, 2012) (Hattori et al, 2016) Ranitidine Blocker 36-94 ng/ml (IC50) Fed at 1.5 mg/30 g body weight Reduced renal damage and attenuated atherosclerosis in a HFD mouse model (Liu et al, 2020) Cimetidine Antagonist 70 nM (Ki) IP injection of 150 mg/kg (Estaphan et al, 2015); 0.25-1.2 mM addition to cell-free extract (Minai-Tehrani et al, 2011) Decreased creatinine, BUN, K + , Na + , NO, blood pressure creatine kinase, increased GFR, urine volume, and renal glutathione (Estaphan et al, 2015); improved renal function when used in combination with L-carnitine in a rat model of glycerol induced acute renal failure (Minai-Tehrani et al, 2011) epithelial cells equipped with histamine synthesis machinery. Thus, antagonism of histamine receptors has been proposed for the management of cardiac damage in hypertensive diseases (Potnuri et al, 2018).…”
Section: (Pki)mentioning
confidence: 99%
“…Oral gavage, 20 mg/kg/day dissolved in 2 ml saline (Sahin et al, 2019); Orally via catheter, 20 mg/kg (Tok et al, 2012) Ameliorated glomerular and tubular histology, decreased kidney expression of caspase-1 and fraction of TUNEL-positive cells (apoptosis) and kidney expression of NLRP3 and IL-1β (inflammation) in a rat model of diabetes (Sahin et al, 2019); reduced levels of lipid peroxidation and oxidative injury products in renal tissue, improved histological appearance in a rat I/R model (Tok et al, 2012) (Hattori et al, 2016) Ranitidine Blocker 36-94 ng/ml (IC50) Fed at 1.5 mg/30 g body weight Reduced renal damage and attenuated atherosclerosis in a HFD mouse model (Liu et al, 2020) Cimetidine Antagonist 70 nM (Ki) IP injection of 150 mg/kg (Estaphan et al, 2015); 0.25-1.2 mM addition to cell-free extract (Minai-Tehrani et al, 2011) Decreased creatinine, BUN, K + , Na + , NO, blood pressure creatine kinase, increased GFR, urine volume, and renal glutathione (Estaphan et al, 2015); improved renal function when used in combination with L-carnitine in a rat model of glycerol induced acute renal failure (Minai-Tehrani et al, 2011) epithelial cells equipped with histamine synthesis machinery. Thus, antagonism of histamine receptors has been proposed for the management of cardiac damage in hypertensive diseases (Potnuri et al, 2018).…”
Section: (Pki)mentioning
confidence: 99%
“…14 ALP has a hydrolase group and is responsible for removing phosphate groups from many types of molecules. 15 Thus, the enzyme may have triggered the release of phosphate from bone Abbreviations: SD, standard deviation; SEM, standard error of the mean; CI, confidence interval; df, degrees of freedom; Sig., significance (2-tailed significance); AST, aspartate aminotransferase; ALT, alanine aminotransferase; LDH, lactate dehydrogenase; ALP, alkaline phosphatase; CK, creatine kinase; CK-MB, creatine kinase muscle and brain; Na þ , the positively charged sodium ion; K þ , the positively charged potassium ion; Cl À , the negatively charged chlorine ion. tissue with increasing muscle contraction.…”
Section: Discussionmentioning
confidence: 99%
“…14 ALP has a hydrolase group and is responsible for removing phosphate groups from many types of molecules. 15 Thus, the enzyme may have triggered the release of phosphate from bone tissue with increasing muscle contraction. 16 The significant increasing was seen in the ALP activities of the experimental groups with honey dose-dependent (120.750-215.250 U/L; R 2 = 0.974, P < .05) when compared with the control group.…”
Section: Discussionmentioning
confidence: 99%
“…202 Cimetidine (84), a histamine H2-receptor antagonist (clinically used for the treatment of gastrointestinal diseases) was found to have inhibitory effect on mouse renal AP activity with K i and IC 50 values of 0.5 and 0.52 mM, respectively. 203 It was found that methylenebisphosphonic acid moieties integrated on to calix4arene scaffold were able to inhibit bovine IAP. Inhibition constant K i of calix4arene bis(methylenebisphosphonic) acid (85) at pH 9.0 against bovine IAP was found to be 0.38 μM.…”
Section: Alkaline Phosphatase Inhibitorsmentioning
confidence: 99%